Taguchi optimization of hardness properties and study the effect on microstructural features of SiC reinforced composite coating duplex stainless steel - Paijan, Lailatul Harina; Ali, Mohd Basri; Mamat, Mohd Fauzi; Abu Bakar, Mohd Hadzley; Osman, Mohd Hairizal; Abd Maleque; Asari, Mohd Rashidi (Universiti Putra Malaysia, 2022)
Durability and strength of the materials engineering are major properties that might lead to component failure or diminish their operational especially in tribological applications. One approach to avoid this limitation is to perform a surface modification to protect thematerial from degradation. Hardness is one of the important metallurgical tests for any metallic materials which may result from different manufacturing and treatment processes. In the present work, the hardness behavior of silicon carbide (SiC) reinforced composite coated duplex stainless steel fabricated using tungsten inert gas (TIG) torch cladding was investigated. The process parameters of TIG torch technique were optimized using Taguchi L9 orthogonal array design of experiments. The important parameters that directly related to the energy input on the surface melting during cladding are taken into consideration such as welding current, voltage, transverse speed and argon flow rate. The hardness was evaluated using Vickers micro-hardness tester and the microstructural features were analyzed using scanning electron microscopy and the composition of sample was investigated using energy dispersive x-ray. Based on the Taguchi’s experimental design analysis, the results showed that the TIG cladding parameters of 80 A of current, 20 V of voltage, 1.0 mm s-1 welding transverse speed and 25 Lmin-1 argon flow rate are the optimal values for hardnessperformance of the reinforced composite coating with hardness value of 1000 Hv. The microstructural features revealed that the dendrite is formed due to incorporation of SiC ceramic particles on duplex stainless steel (DSS) via TIG torch melting process and this microstructure is responsible to the increment of hardness.